Hubungan Asupan Vitamin B6 dengan Sindrom Pramenstruasi pada Siswi SMP - Carissa Maharani Amry; Purnamawati Tjhin (Fakultas Kedokteran Universitas Trisakti, 2022)
BackgroundMany women complain of uncomfortable symptoms a few days before menstruation in the form of emotional problems to discomfort in the abdominal area, this condition is called premenstrual syndrome. Lack of nutrients, one of which is vitamin B6, is a risk factor for premenstrual syndrome. This study was conducted to assess the relationship between vitamin B6 intake and premenstrual syndrome in junior high school students. MethodsThe study used an analytical observational method with a cross-sectional design, in 162 students of SMPN 75 Jakarta, which was taken with cluster random sampling and simple random samplingtechniques. Measurement of the incidence of premenstrual syndrome was carried out using sPAF questionnaires and vitamin B6 intake using SQ-FFQ questionnaires. The data from the study were analyzed using the chi-square test. The research was conducted after obtaining the approval of the number ethics 7/KER-FK/II/2022. ResultsThe results showed that female students who experienced premenstrual syndrome were mostly aged 15-16 years (20.8%), had menarche at the age of under 12 years (16.4%), did less exercise (15.6%), had a body mass index (BMI) in the category of excess nutrition (25.0%), and consumed foods that contained enough vitamin B6 (15.0%). The results of the bivariate analysis between free and dependent variables found no meaningful relationship between premenstrual syndrome and age (p = 0.054), menarche age (p = 0.630), exercise (p = 0.726), BMI (p = 0.131), and vitamin B6 intake (p = 1.000). ConclusionsThere was no relationship between vitamin B6 intake, sociodemographic characteristics (age, menarche age), exercise, and body mass index (BMI) and premenstrual syndrome.